Learning Path HTML5 Fundamentals - Roumeliotis, Rachel (O'Reilly Media, Incorporated, 2015)
Build great sites and applications for any platform HTML5 lets you program for features, not browser versions, giving you much more control and flexibility over your sites and apps while freeing you from worrying about the quirks of any specific platform. Learn how to create impressive, interactive websites and web apps that include video and audio, dynamic drawings, geolocation, offline availability, drag-and-drop, and many other features.
Online resource; Title from title screen (viewed September 21, 2015)
Keywords: Internet videos; Streaming video; Vidéos sur Internet; Vidéo en continu; streaming video; Electronic videos